Impact of Treasury Single Account Policy on University Revenues: A Case Study of the University of Jos, Nigeria - Sadiq, Yahaya Abubakar; Abdullahi, Usman Yakubu; Sule, Kabiru (Kashere Journal of Politics and International Relations, 2024)
This study examined the impact of the Treasury Single Account (TSA) policy on the revenues of the University of Jos and its role in reconciling fund balance differences between the government and the university. The study assessed the implications of the TSA policy on financial operations and accountability within the university context. This study employed descriptive survey design. The population for this study included administrators, financial officers, and relevant staff at the University of Jos. Government officials involved in the implementation of the TSA policy were also considered for interviews and data collection. Structured interviews were conducted with key stakeholders to gather qualitative insights into the impact of the TSA policy. Financial records, government policies, and relevant documents were analyzed to understand the implementation and effects of the TSA policy. Questionnaires were distributed to a sample of university staff to collect quantitative data on their experiences with the TSA policy. Qualitative data from interviews and document analysis were subjected to content analysis to identify recurring themes and patterns. Quantitative data were analyzed using statistical techniques, such as descriptive statistics and simple percentage, to identify trends and correlations. The findings provided insights into financial management, transparency, and accountability within the university. Based on the findings, the study recommended improvements in financial reporting, communication between the university and the government, and the development of strategies to mitigate any adverse effects on university revenues.